Keberkesanan program keusahawanan dan transformasi nelayan di Pulau Langkawi, Kedah - Abdul Jabbar, Mohamad Yusuff (2020)
Malaysian government had long been focusing in driving the economic transformation agenda for coastal fishing community due to the uncertain income generation and the inability to improve their economic levels above their subsistence needs. Although various fisherman development programmes had been implemented, it was found that did not have the impact that could change their livelihood. This study was able to explain the problems faced by fishermen in Langkawi Island who had joined Zone A Fishermen’s Income Increase Programme (cage culture farming). Therefore, the objectives of this study were to identify the problems faced by the participants joining this programme, to analyse the effectiveness of the programme, and to determine the changes in income generation of the participants. This study was done quantitatively and had involved a total of 30 respondents consisting the fishermen who had participated in the programme and sampled through stratified sampling. A pilot study has been carried out to make sure that the respondents understood the given questions well. The data was obtained through interview method and tested using descriptive test to get the demographic distribution of respondents. The findings show that there are three variables (income gained; savings; programme effects) which are found to affect the economic change of participants after participating in the programme, seven variables (input assistances; revolving capital; water quality; lack of skills; participant relationship; motivation; advisory services) are found to affect the implementation of the programme and four variables (aquaculture activities; adequate aquaculture input; economic level; programme affects) are found to affect the effectiveness of the fisherman’s improvement programme. The findings of the study show that the fishing community should be prepared and need to strive to improve themselves so that their lives will improve. The government should also play an important role in helping the fishing community to increase their income. Therefore, the improvement of more planned and controlled programmes need to be suggested so that each of the programme will be more effective and gives a positive impact especially to the target group.